Body mass index and atrial fibrillation recurrence post ablation: A systematic review and dose-response meta-analysis - Liu, Fuwei; Song, Tiangang; Hu, Qingwen; Zhu, Xin; Zhao, Huilei; Tan, Ziqi; Yu, Peng; Ma, Jianyong; Luo, Jun; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2023)
Objectives: The aim of this study was to evaluate the shape of the dose-response relationship between body mass index (BMI) and atrial fibrillation (AF) recurrence in patients who have undergone radiofrequency ablation. Methods: Studies investigating BMI and AF recurrence in patients with AF after ablation were identified through electronic searches in the PubMed, EMBASE, and Cochrane Library databases. The potential nonlinear relationship was fitted using robust error meta-regression. Our study was registered with PROSPERO (CRD42019121373). Results: Twenty-six cohort studies with 7,878 cases/26,450 individuals were included, and a linear dose-response relationship between BMI and AF recurrence (Pnon-linearity=0.12) was found. The risk of AF recurrence in patients with a BMI over 28 was significantly increased. Specifically, for each 5 kg/m2 increase in BMI, the risk of AF recurrence increased by 15% (95% CI: 1.08-1.22) with moderate heterogeneity (I2=53%). Subgroup analyses showed that the pooled risk ratio was not significantly changed in subgroup analysis adjustment for the following important potential intermediate factors: left atrial diameter and obstructive sleep apnea. Conclusion: This study showed that there is a borderline positive linear association between BMI and AF recurrence post ablation. Overweight and obesity are significantly associated with AF recurrence.